Themes From Currently Incarcerated Individuals About How to Close the School-to-Prison Pipeline - King, Sanna (The prison journal, 2025)
The school-to-prison pipeline (STPP) is a metaphor for the pathway through which individuals are “pushed” out of school and into the criminal justice system. Research suggests that the disproportionate representation of marginalized groups in the STPP has important implications for their incarceration experiences as adults. Nevertheless, no research of which we are aware asks incarcerated individuals to provide recommendations to deal with the STPP. We use qualitative data from approximately 500 individuals incarcerated in a Southeastern state to gain insight about their recommendations for improving disciplinary practices in school settings. Themes that emerged from their responses include the importance of communication between students and teachers and various support programs. Important racial differences in the themes also exist.